Reading Billy:: Memory, Time, and Subjectivity in The Collected Works of Billy the Kid - Bethell, Kathleen (Studies in Canadian Literature / Études en littérature canadienne, 2003)
In The Collected Works of Billy the Kid, as in much of Michael Ondaatje's work, identity loses diachronic stability with each historical, critical, or reminiscently interpretive reading. The fragments which appear without authorial identification remind us that truth is something we have to guess at; in many cases in the volume, the missing identifiers could refer to either Billy the Kid or Pat Garrett. Ondaatje's discontinuous blend of myth, reminiscence, and occasional fact become, for the reader, a tangible demonstration that time, memory, and subjectivity are inescapable culprits in obscuring our view of the past.